An in vitro approach to determine the human relevance of anti-spermatogenic effects of 4-methylmorpholine 4-oxide, monohydrate (NMMO) in rat reproductive toxicity studies. (August 2022) - Clewell, Rebecca A.; Clewell, Harvey J.; Linakis, Matthew W.; Easley, Charles A.; Langmo, Jacqueline N.; Salley, Joshua; Gentry, Robinan; Rücker, Thomas
Abstract: Reduced sperm counts have been observed in male rats in an extended one generation reproductive toxicity study (EOGRTS, OECD 443) following repeated administration of 300 mg/kg/day N-Methylmorpholine N-oxide (NMMO). However, no adverse effects on reproductive organs have been reported in studies conducted with NMMO, and the mode of action (MOA) for the effects of NMMO on spermatogenesis is unknown, which complicates the interpretation of these data for human risk assessment. Here, a New Approach Method (NAM) strategy was used to evaluate NMMO MOA and compare interspecies susceptibility for anti-spermatogenic effects using organotypic in vitro assays combined with in vitro metabolism and in vitro to in vivo extrapolation (IVIVE) biokinetic modeling to compare predicted oral equivalent doses (OEDs) in human and rat. Dose-response data were collected in isolated germ cells and in an ex vivo seminiferous tubule model that recapitulates the interaction between the somatic environment and differentiating germ cells to account for potential direct and indirect effects on germ cells. With regard to direct spermatogenic effects, the human isolated germ cell model showed no toxicity at doses ≤300 μM (OED ≤ 86 mg/kg/day). With regard to indirect effects, the rat ex vivo model demonstrated dose-dependent decreases in secondary spermatocyte populations at OEDs ≥89 mg/kg/day, and reduced expression of RNAs specific to several stages of spermatogenesis (spermatogonia, pachytene spermatocytes, round spermatids) at OED = 267 mg/kg/day, consistent with in vivo observations. In contrast, the monkey ex vivo model did not show dose-dependent decreases in these same RNAs, and often demonstrated increased trends instead. These studies demonstrate clear quantitative and qualitative differences in the rat and primate response to NMMO. Furthermore, effects observed in the rat in vitro culture were not observed in the monkey at concentrations equivalent to in vivo doses of up to 1376 mg/kg/day, which is higher than the in vivo dose limit in the EOGRT study, indicating that the isolated findings on spermatogenesis in the rat studies are not likely to be relevant to humans. Highlights: In vitro approach for evaluating human relevance of reduced sperm counts in the rat Organotypic spermatotoxicity assays to compare rat, monkey and human responses In vitro to in vivo extrapolation of metabolism to relate effects to administered dose Clear quantitative and qualitative differences in the rat and primate responses Spermatotoxicity observed in the rat is unlikely to be relevant to humans